2005
DOI: 10.1124/jpet.105.083543
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Neurotrophic Agent, T-817MA [1-{3-[2-(1-Benzothiophen-5-yl) Ethoxy] Propyl}-3-azetidinol Maleate], Attenuates Amyloid-β-Induced Neurotoxicity and Promotes Neurite Outgrowth in Rat Cultured Central Nervous System Neurons

Abstract: Progressive neuronal loss in Alzheimer's disease (AD) is considered to be a consequence of the neurotoxic properties of amyloid-␤ peptides (A␤). T-817MA (1-{3-[2-(1-benzothiophen-5-yl) ethoxy] propyl}-3-azetidinol maleate) was screened as a candidate therapeutic agent for the treatment of AD based on its neuroprotective potency against A␤-induced neurotoxicity and its effect of enhancing axonal regeneration in the sciatic nerve axotomy model. The neuroprotective effect of T-817MA against A␤(1-42) or oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…[266] As a final remark, neuroprotective agents have also been developed. 1-{3-[2-(1-benzothiophen-5-yl)ethoxy]propyl}azetidin-3-ol maleate (T-817MA) [267] is now in phase IIa trials in patients with mild to moderate AD.…”
Section: Immunotherapeutic Approachesmentioning
confidence: 99%
“…[266] As a final remark, neuroprotective agents have also been developed. 1-{3-[2-(1-benzothiophen-5-yl)ethoxy]propyl}azetidin-3-ol maleate (T-817MA) [267] is now in phase IIa trials in patients with mild to moderate AD.…”
Section: Immunotherapeutic Approachesmentioning
confidence: 99%
“…In vitro, T-817MA exerts neuroprotective actions against neurotoxicity induced by amyloid-β peptide or hydrogen peroxide in the coculture of cortical neurons with glia cells. It also promotes neurite outgrowth both in the hippocampal slice and cortical reaggregation culture from rats (Hirata et al 2005). Fukushima et al (2006) reported that T-817MA ameliorates sodium nitroprusside-induced mitochondrial dysfunction in rat cortical neurons.…”
Section: Introductionmentioning
confidence: 97%
“…T-817MA (1-{3-[2-(1-benzothiophen-5-yl) ethoxy] propyl} azetidin-3-ol maleate) is a novel compound, and is suggested to be useful for ameliorating symptoms of neurodegenerative disorders, such as Alzheimer's disease (Hirata et al 2005;Nguyen et al 2007). In vitro, T-817MA exerts neuroprotective actions against neurotoxicity induced by amyloid-β peptide or hydrogen peroxide in the coculture of cortical neurons with glia cells.…”
Section: Introductionmentioning
confidence: 99%
“…A second group of squid was fed twice (at a 24-h interval) 0.25 ml of 36.8 mmol l Ϫ1 T-817. T-817 is a neuroprotective compound developed by Toyama Chemical of Japan (Hirata et al, 2005).…”
Section: Pharmaceuticalsmentioning
confidence: 99%